Oxygen reduction reaction catalyzed with titanyl phthalocyanines in nonaqueous and aqueous media - Demir, Faruk; Erdogmus, Ali; Koca, Atif (ROYAL SOC CHEMISTRY, 2013)
Electrochemical and in situ spectroelectrochemical behaviors and electrocatalytic reduction of molecular oxygen with titanyl phthalocyanines (TiPc) bearing 3,4-(methylenedioxy)-phenoxy substituents were performed in aprotic solvents. Multi electrons and metal-based and ring-based redox processes of TiPcs indicate their possible electrocatalytic activity toward many target species. Different numbers and positions of the substituents of the complexes affect the peaks' character and assignment of the processes. The presence of O-2 in the electrolyte system influences the electrochemical and spectral responses of TiPcs. Electrochemical and in situ spectroelectrochemical analysis indicates interaction of molecular oxygen with TiPcs and these interaction mechanisms depend on both the substituent environments of the complexes and the electrolyte system. Langmuir-Blodgett films of the complexes also catalyze molecular oxygen in aqueous media, which is a desired property for their practical application.
Keywords: SITU SPECTROELECTROCHEMICAL CHARACTERIZATION; LANGMUIR-BLODGETT-FILMS; HYDROGEN EVOLUTION; GRAPHITE-ELECTRODES; ELECTROCATALYTIC ACTIVITY; IRON PHTHALOCYANINES; CARBON-MONOXIDE; COBALT; ACID; MANGANESE; Chemistry; Physics